1972
DOI: 10.1111/j.1748-5827.1972.tb06872.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of surgical treatment for thoracolumbar disc protrusion*

Abstract: Ninety‐nine dogs were treated by hemilaminectomy for thoracolumbar intervertebral disc protrusion. Most animals were 4–7 years old and chondrodystrophoid. The incidence of protrusion was higher at the thoracolumbar junction. Animals with paresis, pain, or pain and paresis had a greater recovery rate than dogs with paralysis. Résumé. La protrusion du disque intervertébral thoracolombaire a été traitée par hémi‐laminectomie chez 99 chiens, la plupart âgés de 4 à 7 ans et atteints de chondrodystrophie. Les protr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

1976
1976
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 1 publication
2
20
0
2
Order By: Relevance
“…Our data support the consensus from previous studies indicating that presence or absence of CPP is the most important prognostic factor for functional recovery from SCI 5, 6, 12, 13, 14, 15. Indeed, we found that loss of CPP seems to be an indicator for poor recovery in dogs with L4‐S3 SCI (1/13 dogs recovered within 3 weeks, and 3/11 had a long‐term successful outcome).…”
Section: Discussionsupporting
confidence: 91%
“…Our data support the consensus from previous studies indicating that presence or absence of CPP is the most important prognostic factor for functional recovery from SCI 5, 6, 12, 13, 14, 15. Indeed, we found that loss of CPP seems to be an indicator for poor recovery in dogs with L4‐S3 SCI (1/13 dogs recovered within 3 weeks, and 3/11 had a long‐term successful outcome).…”
Section: Discussionsupporting
confidence: 91%
“…In a study by Penning et al (2006), thoracic dysfunctions were most often observed in the Th13-L1 segment (34.3%), followed by the Th12-Th13 region (28.4%). Other authors reported the highest incidence of 5 displacements in the Th12-L2 region (Knecht 1972, Gage 1975, Brown et al 1977, Macias et al 2002. Pathological changes in this section of the spine are accompanied by severe clinical symptoms due to the low ratio of spinal cord area to spinal cord diameter but in the Th2-Th10 region, displacement in the cranial direction is rarely noted due to the presence of intercapital ligaments which support the spinal canal (Fig.…”
Section: Intervertebral Disc Degenerationmentioning
confidence: 93%
“…In our hospital, IVDD accounts for approximately 200 cases each year. Surgical removal of extruded disc material is the most commonly recommended treatment for dogs with chronic or recurrent clinical signs, paraplegia, and/or severe back pain [7,19,31,34]. Rapid and accurate pre-operative localization of the extruded disc material is important for minimizing anesthesia-related hypotension and further reduction of spinal cord blood flow, minimizing the time required for surgical exposure, minimizing surgical manipulation injury of the spinal cord, and maximizing complete removal of disc fragments [34].…”
Section: Introductionmentioning
confidence: 99%